Quality of beer from historical and current varieties of spring barley with addition of valerian and hops - Némethová, Michaela; Psota, Vratislav; Gregor, Tomáš (KVASNY PRUMYSL, 2024)
Historic spring barley varieties can be a source of resistance to abiotic (drought) and biotic (diseases) environmental factors in breeding programs. They can be a source of the new technological characteristics of malt or sensory characteristics of beer. Beers made from Pilsner malt from two historical varieties – Chlumecky (1902) and Stupicky Starocesky (1926) and two contemporary varieties – Bojos and Sebastian (2005) were evaluated. These beers have been flavoured with valerian, which in combination with hops has been shown to have anxiolytic and sedative effects. A comparison of elementary and sensory parameters of beers with addition of 0.5 g.L-1 and 1.5 g.L-1 of valerian to two different series of beers was carried out. The Chlumecky samples had the lowest content of alcohol by volume (6.17% and 5.12%) in both batch series of beer and the highest real extract in the first batch series (4.11%). The samples of beer from the Stupicky Starocesky variety had low real extract (3.57% and 3.60%) and high content of alcohol by volume in both batch series (6.34% and 5.96%). In terms of sensory analysis it means that beers brewed from the malt made from the older barley varieties – Chlumecky and Stupicky Starocesky with addition of 0.5 g.L-1 of valerian had the highest overall impression.